Assembling a big mosaic: A review of recent books on electronic Human Resource Management (e-HRM) - Stefan Strohmeier (Zeitschrift für Personalforschung (ZfP), 2012)
This paper aims to review recent academic books on general e-HRM. Mapping major academic responsibilities, books on researching, teaching and also practicing e-HRM are reviewed. To this end, brief outlines of the current states of researching, teaching and practicing e-HRM are given and books are reviewed referring to their contributions to the respective state of knowledge. – – Der vorliegende Beitrag dient der Rezension von Büchern zum elektronischen Personalmanagement (e-HRM), wobei Werke zur Forschung, Lehre und Praxis des elektronischen Personalmanagements berücksichtigt werden. Dazu wird zunächst der gegenwärtig Stand von Forschung, Lehre und Praxis des elektronischen Personalmanagements jeweils kurz skizziert und anschließend untersucht, welchen Beitrag entsprechende Bücher zum jeweiligen Stand des Wissens liefern.
Keywords: M12; M15; M59; 650; electronic HRM (e-HR[M]); Human Resource Information Systems; virtual HRM; web-based HRM; book review; Elektronisches Personalmanagement; Bibliometrie